STRUCTURAL RESPONSE OF OFFSHORE BLAST WALLS UNDER ACCIDENTAL EXPLOSION - RAHMAN, SHAIKH ATIKUR (2015)
In order to provide adequate blast protection for on-board personnel and critical equipment against any accidental explosion, stainless-steel profile panels commonly known as blast walls are widely installed on offshore platforms. Offshore blast walls are usually non-load bearing members and are connected with primary steelwork for support. These walls are likely to display significant plastic deformation, hazardous failure or even blowout when exposed to high magnitude blast loading. Most of the operational blast walls were designed by simplified analysis techniques like single degree of freedom (SDOF) as recommended in common blast design guidelines, where damage criterion is usually defined in terms of global deformation or displacement response. Metal walls or thin plate structures like blast wall when subjected to blast impact, may damage severely in a particular region without experiencing a significant global deformation.